MENELUSURI KARAKTERISTIK MAHASISWA DI ERA MASYARAKAT 5.0 STUDI TENTANG DAMPAK TEKNOLOGI DAN DIGITALISASI DI UNIVERSITAS BINA MANDIRI GORONTALO: MENELUSURI KARAKTERISTIK MAHASISWA DI ERA MASYARAKAT 5.0 STUDI TENTANG DAMPAK TEKNOLOGI DAN DIGITALISASI DI UNIVERSITAS BINA MANDIRI GORONTALO - Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2023)
The characteristics of students in general are stability in personality which begins to increase, due to reduced turmoil in feelings. They tend to solidify and think carefully about something they will achieve, so they have a realistic view of themselves and their environment. This research took place at Bina Mandiri University, Gorontalo. The research location is located on Jl. Prof. Dr. Aloe Saboe No. 173, Wongkaditi Village, Kota Utara District, Gorontalo City, Gorontalo Province. On this campus, there are students with diverse cultural backgrounds. Apart from regular classes, the Bina Mandiri Gorontalo University campus also has employee classes (non-regular). The distinctive feature of this campus is the ownership of study programs that are unique and rarely found. This research is a mixed methods research which is a research approach that combines or associates qualitative and quantitative forms, while in qualitative research the steps/stages are broadly divided into three parts, namely; 1) Preparatory/pre-field stages, 2) Field work stages, and 3) Data analysis stages. Quantitative using a Likert scale, this study will look at the characteristics of students in the era of society 5.0 in relation to the impact of technology and digitalization in the learning process in tertiary institutions. The results showed that students at FSTIK had the characteristics of society in the 5.0 era and had an impact of 80.48% on the use of technology and digitalization, students in FEB had an impact of 77.42% and students in FIPB had the characteristics of society in the 5.0 era and then had an impact of 85.08% on the use technology and digitization in the lecture process.